Controlling QCL characterization experiment based on LabVIEW - Wang, Yanyu (Nanyang Technological University, 2022)
Laser technology plays an important role in the modern world and is widely used in many aspects of our daily life. Quantum Cascade Laser (QCL) is a semiconductor injection laser and it focuses on emitting in the mid-infrared and far-infrared regions of the electromagnetic spectrum, achieved by intersubband transitions between quantized states. It has a huge potential and gains a lot of attention in recent years. This Final Year Project (FYP) aims to conduct two electrical and optical characterization experiments of QCL, and here slot single mode QCL will be used. One of the experiments is to get the lasing spectrum using Fourier Transform infrared spectrometer (FTIR), and the other is to do the light intensity/Power-current-voltage (LIV) measurement, and a thermopile detector is used to gather light intensity information. To make both experiments more efficient and safer conducted, a program was developed to control and adjust the electrical parameters of the function generator using LabView 2019, a system-design platform and development environment aimed at graphical design.